Preparation method of high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction
By introducing non-branch aluminum and lactic acid ethanol treatment in the esterification reaction, combined with the formation of nano-silicon dioxide layer, the acidity and stability of the catalyst are improved, and the problems of low activity and recovery of existing catalysts are solved, achieving high efficiency, Stable catalytic performance.
Patent Information
- Application Number
- CN202411272394.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-14
AI Technical Summary
The existing esterification reaction catalysts have problems such as low catalytic activity, strong corrosiveness, many side reactions and difficulty in recycling, especially in industrial applications, which are difficult to meet the needs of high efficiency and stability.
Non-framework aluminum is introduced into the ultra-stable Y-type molecular sieve by loading aluminum nitrate, and post-processed with a mixed solution of lactic acid and ethanol to increase the acid content and acid/Lewis acid ratio, and at the same time form a nano-silica layer on the surface of the molecular sieve to improve Catalyst hydrophobicity and stability.
The prepared mesoporous molecular sieve catalyst has high acid content, excellent hydrophobicity and acid resistance, and has higher catalytic activity than commercial sulfonic acid resins. It has excellent recycling performance and a catalyst recovery rate of more than 98%. It is suitable for esterification reactions and other organic synthesis. process.
Smart Images

Figure CN119303616A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of petroleum processing and petrochemical catalyst application, and specifically relates to a method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction. Background Art
[0002] Esterification reaction and catalyst requirements:
[0003] Esterification is a key process in organic synthesis and is usually carried out by liquid phase catalysis. Inorganic acid catalysts such as sulfuric acid and p-toluenesulfonic acid are widely used in industry. Although they have high catalytic activity, they have some significant disadvantages, such as strong corrosiveness, many side reactions, and difficulty in separation from the reaction mixture. In order to overcome these shortcomings, solid acid catalysts have become an alternative method with high catalytic activity and selectivity, and are easy to recover and reuse.
[0004] Advantages and challenges of solid acid catalysts:
[0005] Ion exchange resin catalysts, including polystyrene-type cation exchange resins and perfluorosulfonic acid resins, show high activity in esterification reactions, but the selective adsorption of reactants and swelling problems limit their industrial applications.
[0006] Solid superacid catalysts, such as ZrO2 and TiO2, have good catalytic activity and selectivity, but poor stability and are difficult to meet the long-term needs of industrial production.
[0007] Zeolite molecular sieve catalysts, such as Y, β and ZSM-5 zeolites, have strong B acid or L acid and good tolerance to high temperature reactions. Dealumination can improve the accessibility of framework aluminum active sites, thereby enhancing catalytic activity.
[0008] Optimization of the physical and chemical properties of zeolite molecular sieve catalysts:
[0009] Acidic site structure: The strength and number of acidic sites in the esterification reaction directly affect the activity of the catalyst. Acid sites (Bromo-acid) are crucial to improving the activity of esterification reactions. The content and strength of Bromo-acid in molecular sieves can be increased by supplementing aluminum and introducing heteropolyacids, thereby improving catalytic performance.
[0010] Porosity: High specific surface area and appropriate pore size help improve the activity and selectivity of the catalyst. Dealumination and desiliconization can be used to construct mesopores in the molecular sieve to improve the mass transfer and diffusion capacity of macromolecular reactants. The pore structure of the molecular sieve can be regulated and the porosity of the catalyst can be improved by using methods such as alkaline desiliconization, steam dealumination, and acid treatment.
[0011] Hydrophobicity: Highly hydrophobic molecular sieves can avoid water poisoning of catalysts, break through chemical equilibrium limitations, and improve conversion rates. Increasing the Si / Al ratio or surface modification of hydrophobic groups are the main methods to achieve hydrophobicity of molecular sieves, and try to achieve hydrophobicity or super hydrophobicity without sacrificing acid site density.
[0012] Future development trends:
[0013] Develop efficient, economical and environmentally friendly catalysts: Future catalyst development should meet the needs of industrial production while taking into account environmental protection and energy-saving factors to prevent environmental pollution.
[0014] Optimize acid site structure: Through reasonable design and modification of molecular sieves, the strength and number of acid sites can be increased, especially strong Acid sites improve the catalytic performance of the catalyst.
[0015] Improve porosity and hydrophobicity: Continue to optimize the pore structure and surface properties of the molecular sieve, and further improve the porosity and hydrophobicity of the catalyst through methods such as dealumination, desiliconization and surface modification.
[0016] Comprehensive performance improvement: Combine dealumination and aluminum supplementation methods to improve the acidity and stability of the molecular sieve and optimize the physical and chemical properties of the catalyst to achieve higher catalytic activity and recycling performance.
[0017] Through in-depth research and optimization of esterification catalysts, the application prospects of Y-type molecular sieves in esterification reactions are broad. Future research will further enhance its performance to meet the evolving industrial needs. Summary of the invention
[0018] In order to cope with the esterification reaction, the molecular sieve catalyst has a strong The present invention aims to provide a method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction, aiming to solve the problems of low catalytic activity, strong corrosiveness, many side reactions and difficulty in recovery of traditional esterification reaction catalysts. By optimizing the physical and chemical properties of molecular sieves, efficient, stable and recyclable catalysts can be obtained, which can effectively meet the requirements of industrial esterification reactions for catalyst efficiency and stability.
[0019] The technical solution of the present invention is:
[0020] A method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction comprises the following steps: firstly, non-framework aluminum is introduced into an ultra-stable Y-type molecular sieve with a low silicon-aluminum ratio by a method of loading aluminum nitrate, wherein the loading amount of aluminum on the ultra-stable Y-type molecular sieve is 0.1-10wt.%, so as to provide a sufficient active aluminum source; then, the ultra-stable Y-type molecular sieve with the non-framework aluminum introduced is post-treated by a mixed solution of lactic acid and ethanol, wherein the molar ratio of lactic acid to ethanol solution is 0.3:1-5:1, the treatment temperature is 50-100°C, the treatment time is 1-20 hours, and the addition time is increased. Acid content and Acid / Lewis acid ratio; or in the above post-treatment process, a silicon source is added to the reaction solution, and the amount of the silicon source added is 0.5:100 to 20:100 according to the mass ratio of silicon atoms to ultra-stable Y-type molecular sieve, and a nano-silica layer is formed on the surface of the molecular sieve to enhance the hydrophobicity and stability of the catalyst in an acidic system.
[0021] The method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction introduces non-framework aluminum into an ultra-stable Y-type molecular sieve containing no or only a small amount of non-framework aluminum by a method of loading aluminum nitrate, and post-treats the ultra-stable Y-type molecular sieve introduced with non-framework aluminum by a mixed solution of lactic acid and ethanol. The prepared mesoporous molecular sieve catalyst has high Acid content: 0.10~0.60mmol·g -1 and higher The acid / Lewis acid ratio is 53~∝.
[0022] The method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction comprises adding a silicon source to a mixed solution of lactic acid and ethanol during post-treatment to prepare a mesoporous molecular sieve catalyst containing only A mesoporous molecular sieve catalyst with a nano-silica layer on its surface.
[0023] The method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction has excellent catalytic activity and recycling performance in the esterification reaction, the catalytic activity is higher than that of commercial sulfonic acid resin and heteropoly acid, and the catalyst recovery rate during its recycling process is greater than 98%.
[0024] The method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction uses an ultra-stable Y-type molecular sieve with a mesoporous structure, a silicon-aluminum atomic ratio of 4 to 8, no or a small amount of non-framework aluminum, and the content of non-framework aluminum is less than 10wt% of the total aluminum content.
[0025] The method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction, and the method for introducing non-framework aluminum into the ultra-stable Y-type molecular sieve are as follows: first, the ultra-stable Y-type molecular sieve is added to an aqueous solution of aluminum nitrate with a concentration of 2.5 to 50 mmol / L, and stirred at 60°C until evaporated to dryness, or the sample is centrifuged and washed with deionized water until the centrifuge is neutral; then dried in an oven at 100°C for 12 hours, and calcined in a muffle furnace at 400 to 600°C, and the loading amount of aluminum on the ultra-stable Y-type molecular sieve is preferably 0.5 to 5wt.%.
[0026] The method for preparing the high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction comprises the following steps: adding the silicon source during the post-treatment of lactic acid and ethanol solution; the silicon source comprises tetraethyl orthosilicate, silica sol or white carbon black; and the amount of the silicon source added is preferably 1:100 to 10:100 in terms of the mass ratio of silicon atoms to ultra-stable Y-type molecular sieve.
[0027] In the method for preparing the high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction, preferably, the molar ratio of lactic acid to ethanol solution is 0.5:1 to 3:1, the treatment temperature is 60 to 95° C., and the treatment time is 3 to 7 hours.
[0028] The method for preparing the high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction has a high specific surface area of 700 to 1000 m2·g -1 , micropore volume is 0.2~0.4cm3·g -1 , mesopore volume is 0.2~0.4cm3·g -1 The appropriate mesopore diameter is 2 to 50 nanometers. Mesopores are constructed in the molecular sieve by dealumination and aluminum insertion to improve the mass transfer and diffusion capacity of macromolecular reactants.
[0029] The method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction has excellent hydrophobicity. Hydrophobicity or super-hydrophobicity is achieved by increasing the Si / Al ratio or modifying the surface with hydrophobic groups to avoid water poisoning of the catalyst and improve the conversion rate.
[0030] The present invention mainly focuses on improving the catalytic performance of ultrastable Y-type molecular sieve (USY) in esterification reaction by modifying the USY. The specific design concept is:
[0031] (1) Introduction of non-framework aluminum: Non-framework aluminum is introduced into the ultra-stable Y-type molecular sieve with a low silicon-aluminum ratio by loading aluminum nitrate. The introduced aluminum is active during the esterification reaction and can be inserted into the molecular sieve framework to improve its Acid content.
[0032] (2) Post-treatment of esterification reaction: The ultra-stable Y-type molecular sieve that has been introduced with non-framework aluminum is post-treated by using an esterification reaction system constructed with lactic acid and ethanol to improve the molecular sieve. Acid content and This treatment step will remove the non-framework aluminum and part of the framework aluminum in the original ultra-stable Y-type molecular sieve, insert the added non-framework aluminum into the molecular sieve framework, increase its framework aluminum content, and thus increase its Acid content.
[0033] (3) Introducing silicon source: or in the post-treatment process of the ultra-stable Y-type molecular sieve introduced with non-framework aluminum in the esterification reaction system, adding silicon source (such as tetraethyl orthosilicate, etc.) to the reaction solution, by controlling the amount of silicon source added, a nano-silicon dioxide layer is formed on the surface of the molecular sieve, further improving the catalyst Acid content and acid / Lewis acid ratio, which makes it hydrophobic and stable in acidic systems. By adjusting the reaction conditions, it is also possible to prepare At the same time, a nano-silicon dioxide layer is formed on the surface of the molecular sieve to significantly enhance the hydrophobicity and stability of the catalyst in an acidic system.
[0034] Through these steps, the prepared catalyst has a high Br content, a high Br / L ratio, excellent hydrophobicity and acid resistance, shows higher esterification activity than commercial sulfonic acid resin, and has excellent recycling performance.
[0035] The present invention has the following advantages and beneficial effects:
[0036] 1. Method for introducing non-framework aluminum ultra-stable Y-type molecular sieve by post-esterification treatment: non-framework aluminum is introduced into ultra-stable Y-type molecular sieve containing no or only a small amount of non-framework aluminum by using the method of loading aluminum nitrate. The ultra-stable Y-type molecular sieve introduced with non-framework aluminum is treated with lactic acid and ethanol solution to remove non-framework aluminum and part of the framework aluminum in the original molecular sieve. At the same time, the added non-framework aluminum is inserted into the molecular sieve framework to improve the catalyst. Acid content and Acid / L acid ratio. This treatment method is simple and easy to implement, and the effect is significant.
[0037] 2. Introducing silicon source to improve performance: In the process of introducing non-framework aluminum ultra-stable Y-type molecular sieve in the post-esterification treatment, silicon source (such as tetraethyl orthosilicate, etc.) is added to the reaction solution to form a nano-silica layer on the surface of the molecular sieve, which significantly improves the hydrophobicity and stability of the catalyst in an acidic system, and further improves the catalyst Acid content and Acid / L acid ratio. This innovation significantly enhances the acid corrosion resistance and recycling performance of the catalyst.
[0038] 3. Comprehensive performance improvement: The prepared mesoporous molecular sieve catalyst not only has high Acid content and high The acid / L acid ratio also shows excellent esterification reaction catalytic activity, hydrophobicity, acid corrosion resistance and good recycling performance. Compared with traditional catalysts, the activity and stability of this catalyst are significantly improved, the catalytic activity is higher than that of commercial sulfonic acid resins and heteropoly acids, and the catalyst recovery rate is greater than 98%.
[0039] These innovations demonstrate the significant advantages of this method in the field of esterification catalysts, overcome the shortcomings of traditional catalysts, and provide an efficient, stable and recyclable catalyst preparation method. This catalyst is not only suitable for esterification reactions, but also can be used for etherification reactions, condensation reactions, etc. It has broad application prospects in the fields of oil processing, petrochemicals, fine chemicals, etc., and can significantly improve production efficiency and product quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 USY4 molecular sieve (Al 0.8 XRD patterns of USY4-yh) after different time (y=1, 3, 5, 7).
[0041] Figure 2 The solid-state NMR images of USY4 molecular sieve (Al0.8USY4-yh) with non-framework aluminum added after post-treatment with lactic acid and ethanol solution at different times (y = 1, 3, 5, 7) are shown in Figure 2. 27 Al spectrum.
[0042] Figure 3 XRD patterns of USY4 molecular sieves with different external non-framework aluminum after post-treatment with lactic acid and ethanol solutions.
[0043] Figure 4 The solid-state NMR spectra of USY4 molecular sieves with different extra-framework aluminum were obtained by post-treatment with lactic acid and ethanol solutions. 27 Al spectrum.
[0044] Figure 5 This is the XRD spectrum of the sample obtained by adding a silicon source during the post-treatment of USY4 molecular sieve with non-framework aluminum using lactic acid and ethanol solution.
[0045] Figure 6 The solid-state NMR spectra of the samples obtained by adding silicon source during the post-treatment of USY4 molecular sieve with non-framework aluminum by lactic acid and ethanol solution 27 Al spectrum.
[0046] Figure 7 These are transmission electron microscope photos of the sample obtained by post-treatment with ethyl lactate; (a, b) are samples obtained by post-treatment with ethyl lactate and adding non-framework aluminum to USY4 molecular sieve; (c, d) are samples obtained by post-treatment with ethyl lactate and adding a silicon source during the non-framework aluminum process.
[0047] Figure 8 These are the thermogravimetric curves of the sample prepared by post-treatment with ethyl lactate and adding non-framework aluminum to USY4 molecular sieve, as well as the sample prepared by post-treatment with ethyl lactate and adding a silicon source during the non-framework aluminum process after water absorption.
[0048] Fig. 9 This is the XRD pattern of the sample obtained by post-treating the original USY4 molecular sieve with lactic acid and ethanol solution.
[0049] Fig.10 The solid-state NMR of the sample obtained by post-treatment of the original USY4 molecular sieve with lactic acid and ethanol solution 27 Al spectrum.
[0050] Fig.11 The morphology of the sulfonic acid resin before (a) and after (b) the reaction.
[0051] The above experimental results show that the crystallinity of the ultra-stable Y-type zeolite with non-framework aluminum added after treatment with lactic acid and ethanol is significantly improved. After adding a silicon source, the crystallinity of the zeolite is further improved. The crystallinity of the original USY4 zeolite treated with lactic acid and ethanol decreases after esterification. The post-treated sample of USY4 with non-framework aluminum added shows higher catalytic performance in the synthesis of ethyl lactate. After adding a silicon source, the modified sample has higher The acid content and B acid / L acid ratio make the catalytic efficiency higher and have good hydrophobicity. DETAILED DESCRIPTION
[0052] In the specific implementation process, the present invention proposes a method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction, which specifically comprises the following steps: first, non-framework aluminum is introduced into an ultra-stable Y-type molecular sieve containing no or only a small amount of non-framework aluminum by a method of loading aluminum nitrate; then, the ultra-stable Y-type molecular sieve introduced with non-framework aluminum is treated with lactic acid and ethanol solution to obtain a high-activity and high-stability mesoporous molecular sieve catalyst. A mesoporous molecular sieve with a high acid content and a high B acid / L acid ratio; or, in the above-mentioned treatment process, a silicon source is added to the reaction solution to further prepare a mesoporous molecular sieve containing only A mesoporous molecular sieve catalyst with a nano-silica layer on its surface.
[0053] Below, the present invention is further described in detail by examples.
[0054] Example 1
[0055] In this embodiment, the method for preparing the ultra-stable Y-type molecular sieve with added non-framework aluminum is mainly introduced. The specific steps are as follows: 1.5 grams of ultra-stable Y-type molecular sieve containing a small amount of non-framework aluminum (silicon-aluminum atomic ratio is 4, non-framework aluminum content is 9.1wt%, referred to as USY4) are added to 40 ml of aluminum nitrate aqueous solution with concentrations of 0.25, 0.5, 1.0 and 1.3 mmol / L respectively. Stir at 60°C until the solution evaporates to dryness, and dry in an oven at 100°C for 12 hours. The dried sample is placed in a muffle furnace at 500°C for roasting to obtain an ultra-stable Y-type molecular sieve with added non-framework aluminum, i.e., AlxUSY4 molecular sieve (x=0.4, 0.8, 1.6, 2.4, x represents the percentage of added non-framework aluminum in the total mass of the molecular sieve) sample.
[0056] Example 2
[0057] In this example, the effect of post-treatment time on the physicochemical properties and catalytic performance of the ultrastable Y-type molecular sieve with non-framework aluminum added by esterification reaction is mainly introduced. The specific steps are as follows: 1.5 g of USY4 molecular sieve with non-framework aluminum added prepared in Example 1 (i.e., Al 0.8 USY4 molecular sieve, the percentage of added non-framework aluminum in the total mass of the molecular sieve is 0.8%), is slowly added to a mixed solution of lactic acid (0.4 mol) and ethanol (0.4 mol). Stir at a speed of 500 rpm and treat at 65°C for y hours (y represents the treatment time). After treatment, centrifuge and wash with deionized water until the centrifuge is neutral, and dry at 100°C for 12 hours. The dried sample is moved to a muffle furnace at 550°C and calcined for 2 hours to obtain the sample treated by esterification reaction, i.e., Al 0.8 USY4-yh(y=1,3,5,7).
[0058] The experimental process of catalytic performance evaluation is as follows: 0.3 mol of ethanol and 0.3 mol of lactic acid are added to a three-necked flask equipped with a thermometer and a reflux condenser, the catalyst dosage is 1.5 g, the reaction is carried out at 65° C. for 5 hours, and sampling is carried out.
[0059] like Figure 1 As shown, the USY4 molecular sieve (Al 0.8 XRD patterns of USY4-yh) after different time periods (y=1, 3, 5, 7). The figure shows that after the addition of non-framework aluminum, the relative crystallinity of the molecular sieve decreases, but as the post-treatment time increases, the crystallinity of the sample increases significantly until the relative crystallinity is higher than that of the original USY4 molecular sieve.
[0060] like Figure 2As shown, the USY4 molecular sieve (Al 0.8 Solid-state NMR images of USY4-yh) after different time periods (y=1, 3, 5, 7) 27 Al spectrum. The figure shows that after the original USY4 molecular sieve is added with non-framework aluminum, the peak of non-framework aluminum can be clearly seen in the solid NMR aluminum spectrum. As the post-treatment time increases, the characteristic peak of non-framework aluminum disappears, and the characteristic peak of framework aluminum is significantly enhanced.
[0061] As shown in Table 1, the USY4 molecular sieve (Al 0.8 The relative crystallinity and atomic ratio of silicon to framework aluminum of USY4-yh) after different time (y=1, 3, 5, 7). As can be seen from the table, after adding non-framework aluminum, the crystallinity of the molecular sieve decreases slightly, but with the extension of the post-esterification treatment time, the relative crystallinity of the sample continues to increase until it is higher than the crystallinity of the original USY4 molecular sieve. The silicon-aluminum atomic ratio of the sample first increases and then slowly decreases, proving that the transformation of first dealumination and then aluminum insertion occurs during the post-esterification treatment process.
[0062] As shown in Table 2 and Table 3, the NH3-TPD results and Py-FTIR data of USY4 molecular sieve after esterification reaction and addition of non-framework aluminum at different times. It can be seen from the table that as the treatment time increases, The acid / Leis acid ratio gradually increased and reached greater than 53 after 5 hours.
[0063] As shown in Table 4, the physical adsorption data of USY4 molecular sieve after esterification and addition of non-framework aluminum at different times. It can be seen from the table that the micropore volume, mesopore volume and total pore volume of the modified sample increased significantly.
[0064] As shown in Table 5, the yield of ethyl lactate in the synthesis of ethyl lactate catalyzed by the samples obtained after different times of esterification reaction post-treatment with USY4 molecular sieve with non-framework aluminum. It can be seen from the table that the samples with a post-treatment time of 5 to 7 hours have a higher yield of ethyl lactate.
[0065] Example 3
[0066] In this embodiment, the influence of the added aluminum content on the physical and chemical properties of the product during the post-treatment of the ultra-stable Y-type molecular sieve containing non-framework aluminum by esterification reaction is mainly introduced. The specific steps are as follows: 1.5 grams of ultra-stable Y-type molecular sieves with different added aluminum contents prepared in Example 1 (i.e., AlxUSY4 molecular sieves, x=0.4, 0.8, 1.6, 2.4, x represents the percentage of different non-framework aluminum in the total mass of the molecular sieve) are slowly added to a mixed solution of lactic acid (0.4 mol) and ethanol (0.4 mol). Stir at a speed of 500 rpm and treat at 65°C for 5 hours. After treatment, centrifuge the sample and wash it with deionized water until the centrifuge is neutral, and dry it at 100°C for 12 hours. The dried sample was transferred to a muffle furnace at 550°C and calcined for 2 hours to obtain the aluminum-supplemented modified USY4 molecular sieve, namely AlxUSY4-5h (x=0.4, 0.8, 1.6, 2.4, x represents the percentage of different non-framework aluminum in the total mass of the molecular sieve).
[0067] The experimental process of catalytic performance evaluation is as follows: 0.3 mol of ethanol and 0.3 mol of lactic acid are added to a three-necked flask equipped with a thermometer and a reflux condenser, the catalyst dosage is 1.5 g, the reaction is carried out at 65° C. for 5 hours, and sampling is carried out.
[0068] like Figure 3 As shown, the XRD patterns of USY4 molecular sieves with different amounts of added non-framework aluminum after post-treatment with lactic acid and ethanol solutions are shown in FIG. The figure shows that the USY4 molecular sieves with different amounts of added non-framework aluminum after esterification reaction have higher relative crystallinity than the original USY4 molecular sieves.
[0069] like Figure 4 As shown, the solid NMR 27Al spectra of USY4 molecular sieves with different amounts of added non-framework aluminum after post-treatment with lactic acid and ethanol solutions. The figure shows that after esterification reaction, USY4 molecular sieves with different amounts of added non-framework aluminum can effectively convert the added non-framework aluminum into framework aluminum.
[0070] As shown in Table 6, the relative crystallinity and atomic ratio of silicon to framework aluminum of USY4 molecular sieves with different non-framework aluminum added after post-treatment with lactic acid and ethanol solution. As can be seen from the table, after adding non-framework aluminum, the crystallinity of the molecular sieve decreased slightly, but with the extension of the post-esterification treatment time, the relative crystallinity of the sample continued to increase until it was higher than the crystallinity of the original USY4 molecular sieve. The silicon-aluminum atomic ratio of the sample first increased and then slowly decreased, proving that the transition of first dealumination and then aluminum insertion occurred during the post-esterification treatment process.
[0071] As shown in Tables 7 and 8, the NH3-TPD results and Py-FTIR data of USY4 molecular sieves with non-framework aluminum added after esterification reaction at different times. It can be seen from the table that with the increase of the added aluminum content, the total acid content and The acid / Lewis acid ratio gradually increased.
[0072] As shown in Table 9, the physical adsorption data of USY4 molecular sieves after esterification and addition of non-framework aluminum at different times. It can be seen from the table that the modified samples have higher micropore volume, mesopore volume and total pore volume.
[0073] As shown in Table 10, the yield of ethyl lactate in the synthesis of ethyl lactate catalyzed by the USY4 molecular sieve with non-framework aluminum added after esterification reaction was obtained at different times. As can be seen from the table, the sample with an added aluminum content of 1.6-2.4 wt.% has a higher yield of ethyl lactate.
[0074] Example 4
[0075] In this embodiment, a method for preparing a water-enhancing mesoporous Y-type molecular sieve by post-treating an ultrastable Y-type molecular sieve containing non-framework aluminum through an esterification reaction and supplementing silicon is mainly introduced. The specific steps are as follows: add a mixed solution of 0.4 mol of lactic acid and 0.4 mol of ethanol to a 100 ml flask, and slowly add z mmol of tetraethyl orthosilicate (z = 0.1, 0.3, 0.5 mmol) under stirring conditions of 500 rpm. After stirring for 2 minutes, add 1.5 grams of Al0.8USY4 molecular sieve and treat at 65°C for 5 hours. After treatment, centrifuge the sample and wash it with deionized water until the centrifuge is neutral, and dry it at 100°C for 12 hours. The dried sample is moved to a muffle furnace at 550°C and calcined for 2 hours to obtain aluminum-supplemented and silicon-supplemented modified USY4 molecular sieve, namely Al0.8SizUSY4~5h (z=1.4, 4.2, 7.0, z represents the mass percentage of added silicon in the modified molecular sieve).
[0076] The experimental process of catalytic performance evaluation is as follows: 0.3 mol of ethanol and 0.3 mol of lactic acid are added to a three-necked flask equipped with a thermometer and a reflux condenser, the catalyst dosage is 1.5 g, the reaction is carried out at 65° C. for 5 hours, and sampling is carried out.
[0077] like Figure 5 As shown, the XRD spectrum of the sample obtained by adding silicon source during the post-treatment of USY4 molecular sieve with non-framework aluminum by lactic acid and ethanol solution. It can be seen from the figure that the samples obtained by adding silicon source during the post-esterification reaction have higher relative crystallinity than the original USY4 molecular sieve.
[0078] like Figure 6As shown, the solid-state NMR of the sample obtained by adding silicon source during the post-treatment of USY4 molecular sieve with non-framework aluminum by lactic acid and ethanol solution 27 Al spectrum. It can be seen from the figure that the addition of silicon source during the post-esterification treatment process can effectively convert the added non-framework aluminum into framework aluminum.
[0079] like Figure 7 As shown in the figure, the transmission electron microscope photos of the sample obtained by ethyl lactate post-treatment; (a, b) are samples obtained by ethyl lactate post-treatment and adding non-framework aluminum to USY4 molecular sieve; (c, d) are samples obtained by adding silicon source during ethyl lactate post-treatment and adding non-framework aluminum. It can be seen from the figure that the sample obtained by adding silicon source during ethyl lactate post-treatment and adding non-framework aluminum to USY4 molecular sieve has a silicon dioxide layer of about 5 nanometers thick on the surface.
[0080] like Figure 8 As shown in the figure, the thermogravimetric curves of the sample prepared by USY4 molecular sieve with post-treatment of ethyl lactate and addition of non-framework aluminum, and the sample prepared by adding silicon source during post-treatment of ethyl lactate and addition of non-framework aluminum after water absorption. It can be seen from the figure that the sample prepared by adding silicon source has good hydrophobicity.
[0081] As shown in Table 11, the relative crystallinity and the atomic ratio of silicon to framework aluminum of the samples obtained by adding silicon source during the post-treatment of USY4 molecular sieves with different non-framework aluminum added by lactic acid and ethanol solutions. As can be seen from the table, the samples with silicon source added have higher relative crystallinity than the original USY4 molecular sieve, and the silicon-aluminum atomic ratio of the obtained samples increases with the increase of the amount of added silicon, and is higher than the silicon-aluminum atomic ratio of the samples prepared without adding silicon source.
[0082] As shown in Tables 12 and 13, the NH3-TPD and Py-FTIR data of the samples obtained by adding silicon source during the post-treatment of USY4 molecular sieves with different non-framework aluminum using lactic acid and ethanol solutions. It can be seen from the table that compared with the samples prepared without adding silicon source, they all have a higher strong acid / weak acid ratio and contain only Acid, does not contain Lewis acid.
[0083] As shown in Table 14, the physical adsorption data of the samples obtained by adding silicon source during the post-treatment of USY4 molecular sieves with different non-framework aluminum by lactic acid and ethanol solution. It can be seen from the table that compared with the samples prepared without adding silicon source, they all have higher micropore volume and higher total pore volume.
[0084] As shown in Table 15, the yield of ethyl lactate in the catalytic ethyl lactate synthesis of the samples obtained by adding silicon source during the post-treatment of USY4 molecular sieves with different non-framework aluminum using lactic acid and ethanol solution. As can be seen from the table, compared with the samples prepared without adding silicon source, all have higher ethyl lactate yields, among which the sample with 1.6wt.% silicon source added has the highest ethyl lactate yield.
[0085] Example 5
[0086] In this embodiment, a method for preparing a water-enhancing mesoporous Y-type molecular sieve by post-treating an ultrastable Y-type molecular sieve containing non-framework aluminum through an esterification reaction and supplementing silicon is mainly introduced. The specific steps are as follows: add a mixed solution of 0.4 mol of lactic acid and 0.4 mol of ethanol to a 100 ml flask, and slowly drop z mmol of silica sol (z = 0.1, 0.3, 0.5 mmol) under stirring conditions of 500 rpm. After stirring for 2 minutes, add 1.5 grams of Al0.8USY4 molecular sieve and treat at 65°C for 5 hours. After treatment, centrifuge the sample and wash it with deionized water until the centrifuge is neutral, and dry it at 100°C for 12 hours. The dried sample is moved to a muffle furnace at 550°C and calcined for 2 hours to obtain aluminum-supplemented and silicon-supplemented modified USY4 molecular sieve, namely: silica sol-Al0.8SizUSY4~5h (z=1.4, 4.2, 7.0, z represents the mass percentage of added silicon in the modified molecular sieve).
[0087] The experimental process of catalytic performance evaluation is as follows: 0.3 mol of ethanol and 0.3 mol of lactic acid are added to a three-necked flask equipped with a thermometer and a reflux condenser, the catalyst dosage is 1.5 g, the reaction is carried out at 65° C. for 5 hours, and sampling is carried out.
[0088] As shown in Table 16, the yield of ethyl lactate in the synthesis of ethyl lactate catalyzed by adding silica sol as silicon source during the post-treatment of USY4 molecular sieves with different non-framework aluminum using lactic acid and ethanol solution. As can be seen from the table, adding silica sol as silicon source has a higher yield of ethyl lactate than adding tetraethyl orthosilicate as silicon source.
[0089] Example 6
[0090] In this embodiment, a method for preparing a water-enhancing mesoporous Y-type molecular sieve by post-treating an ultrastable Y-type molecular sieve containing non-framework aluminum through an esterification reaction and supplementing silicon is mainly introduced. The specific steps are as follows: add a mixed solution of 0.4 mol of lactic acid and 0.4 mol of ethanol to a 100 ml flask, and slowly add z mmoles of white carbon black (z = 0.1, 0.3, 0.5 mmol) under stirring conditions of 500 rpm. After stirring for 2 minutes, add 1.5 grams of Al0.8USY4 molecular sieve and treat at 65°C for 5 hours. After treatment, centrifuge the sample and wash it with deionized water until the centrifuge is neutral, and dry it at 100°C for 12 hours. The dried sample is moved to a muffle furnace at 550°C and calcined for 2 hours to obtain aluminum- and silicon-supplemented modified USY4 molecular sieve, namely: white carbon black-Al0.8SizUSY4~5h (z=1.4, 4.2, 7.0, z represents the mass percentage of added silicon in the modified molecular sieve).
[0091] The experimental process of catalytic performance evaluation is as follows: 0.3 mol of ethanol and 0.3 mol of lactic acid are added to a three-necked flask equipped with a thermometer and a reflux condenser, the catalyst dosage is 1.5 g, the reaction is carried out at 65° C. for 5 hours, and sampling is carried out.
[0092] As shown in Table 17, the yield of ethyl lactate in the synthesis of ethyl lactate catalyzed by adding white carbon black as a silicon source in the process of post-treatment of USY4 molecular sieves with different non-framework aluminum using lactic acid and ethanol solutions. It can be seen from the table that adding silica sol as a silicon source has a higher yield of ethyl lactate than adding tetraethyl orthosilicate as a silicon source.
[0093] Comparative Example 1
[0094] In this comparative example, the effect of post-treatment time on the physical and chemical properties and catalytic performance of the molecular sieve during the post-treatment of the original ultra-stable Y-type molecular sieve by esterification reaction is mainly introduced. The specific steps are as follows: 1.5 grams of original USY molecular sieve (silicon-aluminum atomic ratio is 4, non-framework aluminum content is 9.1wt%, referred to as USY4 molecular sieve) is slowly added to a mixed solution of lactic acid (0.4 mol) and ethanol (0.4 mol). Stir at a speed of 500 rpm and treat at 65°C for 1 to 7 hours. After treatment, centrifuge the sample and wash it with deionized water until the centrifuge is neutral, and dry it at 100°C for 12 hours. Move the dried sample to a muffle furnace at 550°C and roast for 2 hours to obtain the lactic acid post-treated USY4 molecular sieve.
[0095] The experimental process of catalytic performance evaluation is as follows: 0.3 mol of ethanol and 0.3 mol of lactic acid are added to a three-necked flask equipped with a thermometer and a reflux condenser, the catalyst dosage is 1.5 g, the reaction is carried out at 65° C. for 5 hours, and sampling is carried out.
[0096] like Fig. 9 As shown in FIG. 1 , the XRD pattern of the sample obtained by post-treating the original USY4 molecular sieve with lactic acid and ethanol solution. As can be seen from the figure, the relative crystallinity of the original USY4 molecular sieve after esterification reaction is significantly reduced, and the relative crystallinity is further reduced with the extension of reaction time.
[0097] like Fig.10 As shown in FIG. 27A, solid-state NMR 27Al spectra of the sample obtained by post-treatment of the original USY4 molecular sieve with lactic acid and ethanol solution. As can be seen from the figure, the original USY4 molecular sieve will produce a large amount of non-framework aluminum after esterification reaction.
[0098] As shown in Table 18, the relative crystallinity and atomic ratio of silicon to framework aluminum of the sample obtained by post-treatment of the original USY4 molecular sieve with lactic acid and ethanol solution. As can be seen from the table, the relative crystallinity of the molecular sieve is significantly reduced by post-esterification treatment of the original USY4 molecular sieve, and the relative crystallinity further decreases with the extension of the reaction time.
[0099] As shown in Tables 19 and 20, the NH3-TPD and Py-FTIR data of the samples obtained by post-treatment of the original USY4 molecular sieve with lactic acid and ethanol solutions. It can be seen from the table that the total acid content is greatly reduced compared with the original USY4 molecular sieve, while The acid / Lewis acid ratio did not change significantly.
[0100] The physical adsorption data of the sample obtained by post-treating the original USY4 molecular sieve with lactic acid and ethanol solution are shown in Table 21. As can be seen from the table, the micropore volume is greatly reduced compared with the original USY4 molecular sieve, and the reduction increases with the treatment time.
[0101] As shown in Table 22, the yield of ethyl lactate in the catalytic synthesis of ethyl lactate by the samples obtained by post-treatment of the original USY4 molecular sieve with lactic acid and ethanol solution. As can be seen from the table, the yield of ethyl lactate on the samples prepared by post-treatment decreased compared with the original USY4 molecular sieve.
[0102] Comparative Example 2
[0103] In this comparative example, the catalytic performance of the characteristic sample prepared in the present invention is mainly compared with that of a commercial catalyst: 0.3 mol of ethanol and 0.3 mol of lactic acid are added to a three-necked flask equipped with a thermometer and a reflux condenser, and commercial sulfonic acid resin (Amberlyst-15), commercial phosphotungstic acid, commercial ultra-stable Y (silicon-aluminum atomic ratio of 5), commercial ultra-stable Y (silicon-aluminum atomic ratio of 40), commercial Hβ molecular sieve (silicon-aluminum atomic ratio of 25), and commercial Hβ molecular sieve (silicon-aluminum atomic ratio of 12.5) are added respectively, and the catalyst dosage is 1.5 grams. The reaction is carried out at 65°C for 5 hours, and sampling is carried out for detection.
[0104] As can be seen from Table 23, Al 1.6 Si 4.2 USY4-5h catalyst has much higher catalytic activity for ethyl lactate than commercial molecular sieves, and its catalytic activity is also slightly higher than commercial sulfonic acid resin and phosphotungstic acid. However, phosphotungstic acid does not have the recycling performance and cannot be recycled. After the sulfonic acid resin catalyst reacts, the catalyst changes from granular to powdery ( Fig.11 ), indicating that the catalyst has poor high temperature resistance. At the same time, the catalytic performance also decreases significantly after use, and the catalyst recovery rate is less than 80%. Fig.11 As can be seen from the figure, the commercial sulfonic acid resin absorbs water, expands and breaks during the reaction, and becomes powder after the reaction, which is difficult to recycle and reuse. 1.6 Si 4.2 The performance of USY4-5h catalyst remained stable in the 5-cycle experiment, and the catalyst recovery rate was greater than 98%. It can be seen from the physical adsorption and acid site results of the catalyst before reaction and after 5 cycles in Table 24 and Table 25 that the pore structure and acid site structure of the catalyst remained stable after 5 cycles, which is also the reason for its stable catalytic performance.
[0105] Table 1 Relative crystallinity and atomic ratio of silicon to framework aluminum of USY4 molecular sieve after post-treatment with lactic acid and ethanol solution and addition of non-framework aluminum at different times
[0106] Catalyst Relative crystallinity (%) Si / Al (atomic ratio) USY4 100 4.4 <![CDATA[Al 1.6 USY4]]> 87.8 6.6 <![CDATA[Al 1.6 USY4-1h]]> 70.2 31.2 <![CDATA[Al 1.6 USY4-3h]]> 86.9 27.9 <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 1.6 <h2 style=";text-align:left;direction:ltr"> USY4-5h]]><h2 style=";text-align:left;direction:ltr"> 109.5 26.3 <![CDATA[Al 1.6 USY4-7h]]> 113.2 25.0
[0107] Table 2 NH3-TPD results of USY4 molecular sieve after esterification reaction and addition of non-framework aluminum at different times
[0108]
[0109] a Weakness: 100~350℃; b strong acidity:350~500℃
[0110] Table 3 shows the NH3-TPD and Py-FTIR data of USY4 molecular sieve after esterification reaction and addition of non-framework aluminum at different times
[0111]
[0112] B: acidity (Brønsted acidity), L:Lewis acidity (Lewis acidity); Py-FTIR is pyrolysis-Fourier transform infrared spectroscopy analysis.
[0113] Table 4 Physical adsorption data of USY4 molecular sieve after esterification reaction and addition of non-framework aluminum at different times
[0114]
[0115]
[0116] Table 5 Ethyl lactate yield in the synthesis of ethyl lactate catalyzed by USY4 molecular sieves with non-framework aluminum after esterification reaction for different time periods
[0117] Catalyst <![CDATA[The first cycle 1 s t cycle]]> <![CDATA[Second cycle 2 nd cycle]]> <![CDATA[Third cycle 3 rd cycle]]> USY4 23.0 22.3 21.0 <![CDATA[Al 1.6 USY4]]> 20.3 27.2 27.0 <![CDATA[Al 1.6 USY4-1h]]> 27.8 26.9 26.8 <![CDATA[Al 1.6 USY4-3h]]> 33.5 32.5 32.5 <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 1.6 <h2 style=";text-align:left;direction:ltr"> USY4-5h]]><h2 style=";text-align:left;direction:ltr"> 38.1 37.0 36.9 <![CDATA[Al 1.6 USY4-7h]]> 37.0 35.8 35.3
[0118] Table 6 Relative crystallinity and atomic ratio of silicon to framework aluminum of samples obtained by post-treatment of USY4 molecular sieves with different non-framework aluminum using lactic acid and ethanol solutions
[0119] Catalyst Relative crystallinity(%) Si / Al Al0.4USY4-5h 100.1 30.3 Al0.8USY4-5h 103.6 28.1 Al1.6USY4-5h 109.5 26.3 Al2.4USY4-5h 114.6 24.1
[0120] Table 7 NH3-TPD results of samples obtained by post-treatment of USY4 molecular sieves with different non-framework aluminum using lactic acid and ethanol solutions
[0121] Catalyst <![CDATA[Weakacidity a (mmol·g -1 )]]> <![CDATA[strongacidity b (mmol·g -1 )]]> <![CDATA[Totalacidity(mmol·g -1 )]]> <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 0.4 <h2 style=";text-align:left;direction:ltr"> USY4-5h]]><h2 style=";text-align:left;direction:ltr"> 0.16 0.29 0.47 <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 0.8 <h2 style=";text-align:left;direction:ltr"> USY4-5h]]><h2 style=";text-align:left;direction:ltr"> 0.19 0.31 0.49 <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 1.6 <h2 style=";text-align:left;direction:ltr"> USY4-5h]]><h2 style=";text-align:left;direction:ltr"> 0.21 0.33 0.54 <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 2.4 <h2 style=";text-align:left;direction:ltr"> USY4-5h]]><h2 style=";text-align:left;direction:ltr"> 0.21 0.37 0.58
[0122] a Weakness: 100~350℃; b strongacidity:350~500℃
[0123] Table 8 NH3-TPD and Py-FTIR data of samples obtained by post-treatment of USY4 molecular sieves with different external non-framework aluminum using lactic acid and ethanol solutions
[0124]
[0125] Table 9 Physical adsorption data of samples obtained by post-treatment of USY4 molecular sieves with different external non-framework aluminum using lactic acid and ethanol solutions
[0126]
[0127] Table 10 Ethyl lactate yield in the catalytic ethyl lactate synthesis of samples obtained by post-treatment of USY4 molecular sieves with different non-framework aluminum by lactic acid and ethanol solution
[0128] Catalyst <![CDATA[1 s t cycle]]> <![CDATA[2 nd cycle]]> <![CDATA[3 rd cycle]]> <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 0.4 <h2 style=";text-align:left;direction:ltr"> USY4-5h]]><h2 style=";text-align:left;direction:ltr"> 29.5 29.4 29.4 <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 0.8 <h2 style=";text-align:left;direction:ltr"> USY4-5h]]><h2 style=";text-align:left;direction:ltr"> 31.5 31.9 31.4 <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 1.6 <h2 style=";text-align:left;direction:ltr"> USY4-5h]]><h2 style=";text-align:left;direction:ltr"> 38.1 38.3 38.2 <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 2.4 <h2 style=";text-align:left;direction:ltr"> USY4-5h]]><h2 style=";text-align:left;direction:ltr"> 39.0 38.5 38.6
[0129] Table 11 Relative crystallinity and atomic ratio of silicon to framework aluminum of samples obtained by adding silicon source during post-treatment of USY4 molecular sieves with different non-framework aluminum using lactic acid and ethanol solutions
[0130] Catalyst Relative crystallinity(%) Si / Al <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 1.6 <h2 style=";text-align:left;direction:ltr"> USY4-5h]]><h2 style=";text-align:left;direction:ltr"> 109.5 26.3 <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 1.6 <h2 style=";text-align:left;direction:ltr"> Yes<h2 style=";text-align:left;direction:ltr"> 1.4 <h2 style=";text-align:left;direction:ltr"> USY4-5h]]><h2 style=";text-align:left;direction:ltr"> 108.9 32.5 <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 1.6 <h2 style=";text-align:left;direction:ltr"> Yes<h2 style=";text-align:left;direction:ltr"> 4.2 <h2 style=";text-align:left;direction:ltr"> USY4-5h]]><h2 style=";text-align:left;direction:ltr"> 112.6 36.0 <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 1.6 <h2 style=";text-align:left;direction:ltr"> Yes<h2 style=";text-align:left;direction:ltr"> 7.0 <h2 style=";text-align:left;direction:ltr"> USY4-5h]]><h2 style=";text-align:left;direction:ltr"> 110.0 40
[0131] Table 12 NH3-TPD results of samples obtained by adding silicon source during post-treatment of USY4 molecular sieves with different non-framework aluminum using lactic acid and ethanol solutions
[0132]
[0133] a Weakness: 100~350℃; b Strongacidity:350~500℃
[0134] Table 13 NH3-TPD and Py-FTIR data of samples obtained by adding silicon source during the post-treatment of USY4 molecular sieves with different non-framework aluminum using lactic acid and ethanol solutions
[0135]
[0136] Table 14 Physical adsorption data of samples obtained by adding silicon source during post-treatment of USY4 molecular sieves with different external non-framework aluminum using lactic acid and ethanol solutions
[0137]
[0138] Table 15 Ethyl lactate yield in the catalytic ethyl lactate synthesis of samples obtained by adding silicon source during the post-treatment of USY4 molecular sieves with different non-framework aluminum using lactic acid and ethanol solutions
[0139] Catalyst <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 1.6 <h2 style=";text-align:left;direction:ltr"> USY4-5h]]><h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 1.6 <h2 style=";text-align:left;direction:ltr"> Yes<h2 style=";text-align:left;direction:ltr"> 1.4 <h2 style=";text-align:left;direction:ltr"> USY4-5h]]><h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 1.6 <h2 style=";text-align:left;direction:ltr"> Yes<h2 style=";text-align:left;direction:ltr"> 4.2 <h2 style=";text-align:left;direction:ltr"> USY4-5h]]><h2 style=";text-align:left;direction:ltr"> <h2 style=";text-align:left;direction:ltr"><![CDATA[Al <h2 style=";text-align:left;direction:ltr"> 1.6 <h2 style=";text-align:left;direction:ltr"> Yes<h2 style=";text-align:left;direction:ltr"> 7.0 <h2 style=";text-align:left;direction:ltr"> USY4-5h]]><h2 style=";text-align:left;direction:ltr"> First reaction 38.1 41.6 45.63 42.38 Second reaction 38.3 41.86 45.89 42.38 The third reaction 38.2 41.86 45.89 42.25
[0140] Table 16 Ethyl lactate yield in ethyl lactate synthesis of samples obtained by adding silica sol as silicon source during post-treatment of USY4 molecular sieves with different external non-framework aluminum using lactic acid and ethanol solutions
[0141]
[0142] Table 17 Ethyl lactate yield in the catalytic ethyl lactate synthesis of samples obtained by adding white carbon black as a silicon source during the post-treatment of USY4 molecular sieves with different non-framework aluminum using lactic acid and ethanol solutions
[0143]
[0144] Table 18 shows the relative crystallinity and atomic ratio of silicon to framework aluminum of the sample obtained by post-treating the original USY4 molecular sieve with lactic acid and ethanol solution.
[0145] Catalyst Relative crystallinity (%) Si / Al USY4 100 4.4 USY4-1h 58.8 25.8 USY4-3h 56.0 27.0 USY4-5h 50.6 28.3 USY4-7h 51.7 31.0
[0146] Table 19 shows the NH3-TPD of the sample obtained by post-treatment of the original USY4 molecular sieve with lactic acid and ethanol solution.
[0147] Catalyst <![CDATA[Weakacidity(mmol·g -1 )]]> <![CDATA[strongacidity(mmol·g -1 )]]> <![CDATA[Totalacidity(mmol·g -1 )]]> USY4 0.66 2.32 2.98 USY4-1h 0.21 0.33 0.54 USY4-3h 0.20 0.33 0.50 USY4-5h 0.18 0.29 0.45 USY4-7h 0.18 0.26 0.40
[0148] Table 20 shows the NH3-TPD and Py-FTIR data of the sample obtained by post-treating the original USY4 molecular sieve with lactic acid and ethanol solution.
[0149]
[0150] Table 21 shows the physical adsorption data of the samples obtained by post-treatment of the original USY4 molecular sieve with lactic acid and ethanol solution
[0151]
[0152] Table 22 shows the yield of ethyl lactate in the catalytic ethyl lactate synthesis of the sample obtained by post-treatment of the original USY4 molecular sieve with lactic acid and ethanol solution
[0153] Catalyst <![CDATA[1 s t cycle]]> <![CDATA[2 nd cycle]]> <![CDATA[3 rd cycle]]> USY4-1h 21.2 20.6 20.5 USY4-3h 21.5 21.4 21.5 USY4-5h 22.3 22.3 22.0 USY4-7h 22.4 22.1 22.5
[0154] Table 23A1 1.0 Si 0.3 Yield of ethyl lactate in the cyclic reaction of USY4-5h and commercial catalyst
[0155]
[0156]
[0157] Table 24 Fresh and Al after five cycles 1.6 Si 4.2 Physical adsorption results of USY4-5h samples
[0158]
[0159] Table 25 Fresh and Al after five cycles 1.6 Si 4.2 Acidic site characteristics of USY4-5h samples
[0160]
[0161] The above examples fully demonstrate that by introducing non-framework aluminum and post-treatment methods, the method includes using lactic acid and ethanol to construct an esterification reaction system to treat the ultra-stable Y-type molecular sieve introduced with non-framework aluminum, and adding a silicon source to the reaction solution, and by controlling the reaction temperature, reaction time and other process conditions, a high crystallinity, high silicon-aluminum ratio, high The mesoporous molecular sieve with low acid (B acid) content, no Lewis acid (L acid), hydrophobic and acid-resistant can effectively improve the physical and chemical properties and catalytic performance of ultra-stable Y-type molecular sieve. The unique physical and chemical properties of the molecular sieve make it highly active and have excellent recycling performance in the esterification reaction. In particular, the catalytic efficiency and stability of the molecular sieve can be significantly improved by treating it with lactic acid and ethanol and introducing a silicon source, which has a wide range of industrial application prospects.
Claims
1. A method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction, characterized in that: The invention comprises the following steps: firstly, introducing non-framework aluminum into an ultra-stable Y-type molecular sieve with a low silicon-aluminum ratio by a method of loading aluminum nitrate, wherein the loading amount of aluminum on the ultra-stable Y-type molecular sieve is 0.1-10 wt.%, so as to provide a sufficient active aluminum source; then, post-treating the ultra-stable Y-type molecular sieve with the non-framework aluminum by a mixed solution of lactic acid and ethanol, wherein the molar ratio of the lactic acid to the ethanol solution is 0.3:1-5:1, the treatment temperature is 50-100°C, the treatment time is 1-20 hours, and the addition time is increased. Acid content and Acid / Lewis acid ratio; or in the above post-treatment process, a silicon source is added to the reaction solution, and the amount of the silicon source added is 0.5:100 to 20:100 according to the mass ratio of silicon atoms to ultra-stable Y-type molecular sieve, and a nano-silica layer is formed on the surface of the molecular sieve to enhance the hydrophobicity and stability of the catalyst in an acidic system.
2. The method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction according to claim 1, characterized in that: The non-framework aluminum is introduced into the ultra-stable Y-type molecular sieve containing no or only a small amount of non-framework aluminum by the method of loading aluminum nitrate, and the ultra-stable Y-type molecular sieve introduced with the non-framework aluminum is post-treated by a mixed solution of lactic acid and ethanol. The prepared mesoporous molecular sieve catalyst has high Acid content: 0.10~0.60mmol·g -1 and higher The acid / Lewis acid ratio is 53~∝.
3. The method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction according to claim 2, characterized in that: During the post-treatment of the mixed solution of lactic acid and ethanol, a silicon source is added to the solution to prepare a A mesoporous molecular sieve catalyst with a nano-silicon dioxide layer on its surface.
4. The method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction according to claim 1, characterized in that: The prepared catalyst has excellent catalytic activity and recycling performance in esterification reaction, the catalytic activity is higher than that of commercial sulfonic acid resin and heteropoly acid, and the recovery rate of the catalyst in the recycling process is greater than 98%.
5. The method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction according to claim 1 or 2, characterized in that: The ultra-stable Y-type molecular sieve used has a mesoporous structure, a silicon-aluminum atomic ratio of 4-8, no or a small amount of non-framework aluminum, and the content of non-framework aluminum is less than 10wt% of the total aluminum content.
6. The method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction according to claim 1, characterized in that: The method for introducing non-framework aluminum into the ultra-stable Y-type molecular sieve is as follows: first, the ultra-stable Y-type molecular sieve is added to an aqueous solution of aluminum nitrate with a concentration of 2.5 to 50 mmol / L, and stirred at 60°C until evaporated to dryness, or the sample is separated by centrifugation and washed with deionized water until the centrifuge is neutral; then dried in an oven at 100°C for 12 hours, and calcined in a muffle furnace at 400 to 600°C. The loading amount of aluminum on the ultra-stable Y-type molecular sieve is preferably 0.5 to 5 wt.%.
7. The method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction according to claim 1, characterized in that: The silicon source is introduced as follows: the silicon source is added during the post-treatment of the lactic acid and ethanol solution. The types of silicon sources include ethyl orthosilicate, silica sol or white carbon black. The amount of silicon source added is preferably 1:100 to 10:100 in terms of the mass ratio of silicon atoms to ultra-stable Y-type molecular sieve.
8. The method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction according to claim 1, characterized in that: Preferably, the molar ratio of lactic acid to ethanol solution is 0.5:1 to 3:1, the treatment temperature is 60 to 95° C., and the treatment time is 3 to 7 hours.
9. The method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction according to claim 1, characterized in that: The obtained catalyst has a high specific surface area of 700-1000m 2 ·g -1 , micropore volume is 0.2~0.4cm 3 ·g -1 , mesopore volume is 0.2~0.4cm 3 ·g -1 The appropriate mesopore diameter is 2 to 50 nanometers. Mesopores are constructed in the molecular sieve by dealumination and aluminum insertion to improve the mass transfer and diffusion capacity of macromolecular reactants.
10. The method for preparing a high-activity and high-stability mesoporous molecular sieve catalyst for esterification reaction according to claim 1, characterized in that: The obtained catalyst has excellent hydrophobicity, and hydrophobicity or super hydrophobicity is achieved by increasing the Si / Al ratio or modifying the surface with hydrophobic groups to avoid water poisoning of the catalyst and improve the conversion rate.
Citation Information
Patent Citations
Soil-pulverizer.
US1089325A
Brooder.
US1095263A
Toilet-case.
US1126360A
Gil-more
US1320133A